Parental Risk Factors in Children With Intellectual Disability: An Investigation.: Faktor Risiko Orang Tua Pada Penyandang Disabilitas Intelektual (DI) di Sekolah Luar Biasa (SLB) Palembang - Maritska, Ziske; Arroyantri, Bintang (Sriwijaya Journal of Medicine, 2018)
Intellectual Disability (ID) is a condition where there is a significant disturbance in one’s development including social, cognitive and adaptive function. The prevalence of ID worldwide is varied, whereas its prevalence in South East Asia including Indonesia is quite high. The exact cause of ID is yet to be known. A couple of risk factors are believed to be involved in the occurence of ID. This study aims to identify parental risk factors in children with ID in Special Need School in Palembang. This is a observational descriptive study towards children with ID in Special Need School in Palembang. Primary data were obtained from direct interview and questionnaire filled by parents. Variables being identified were Paternal risk factors (age and smoking habit), Maternal risk factors (age, parity, drug and herbs consumption history during pregnancy, smoking exposure during pregnancy) and family history. There are 68 samples who are mostly male (64.70%) with Mild ID (60.29%). Majority of the Father were <35 years old when they had their child (64.71%) with a smoking habit of 52.94%. Most Mother were age 21-35 years old when pregnant, with parity history of less than 4 (77.94%). Children with ID in Special Need School Palembang showed similar risk factors compared to previous studies. It is hoped that the prevalence of ID can be reduced by preventing the known risk factors.